Analysis of Online Learning in Physical Education, Sports and Health on Learning Outcomes of Class III Students at SD Negeri 03 Air Rami Muko-Muko - Yonatan Rino Nababan; Suwarni Suwarni; Feby Elra Perdima (Penerbit Jurnal Indonesia, 2021)
This study aims to analyze online learning in the subjects of physical education, sports and health on the learning outcomes of third grade students at SD Negeri 03 Air Rami Muko-Muko. Data collection method is a method that can be used by researchers in collecting data. So that in the research obtained information or data relevant to the topic of the problem to be studied. The results of data analysis obtained from online learning scores of students at SD Negeri 03 Air Rami Muko-Muko obtained the highest average score of 99.6, high scores were obtained by 2 students with an average of 89.6 and students who obtained moderate scores. namely 3 people with an average of 85, while students who scored 85 0 students (none). Based on the results of the study, it shows that students' online learning abilities are very good, where each student has a score of 75 (medium) and no one gets a score of 75. This situation shows that the level of students' online learning abilities is good, although the results obtained have experienced the volatility of the value that goes up and down at each assessment. We can see this in the assessments on January 7 and January 11. On January 7, the student's score increased until it reached a score of 100 while on the following date, January 11, the student's score decreased from 100 to 90 even lower on the first assessment on January 4 and experienced changes in the value of up and down until the 6th test later on the last test on the 7th test on January 28, the overall score of students reached 100